Modeling Continuance Intention of Superapps Mobile Banking: An Empirical Study of ECM Extended with Trust and Security - Angelia Natalia; Meita Emba Dwi Mustika; Samuel Indra Christianto Lumba Tobing; Minsani Mariani (Journal Research of Social Science, Economics, and Management, 2025)
Superapps mobile banking is a new type of digital banking service that combines financial transactions and lifestyle aspects into one platform. Superapps are becoming more popular in Indonesia since more people are using the internet and smartphones. This is because there is a rising need for practical and integrated financial solutions. Many studies have looked at the early use of mobile banking, but not many have looked at what keeps people using superapps mobile banking, especially in Indonesia. Using an enhanced Expectation Confirmation Model (ECM), this study intends to look at how perceived security, trust, confirmation, perceived utility, and satisfaction affect the intention to continue using.  We did a survey of 268 people who use superapps mobile banking from regular banks in Indonesia. We then used Partial Least Squares Structural Equation Modeling (PLS-SEM) to look at the data. The results show that confirmation has a beneficial effect on perceived usefulness and satisfaction. Trust and Perceived usefulness seem also to have a big effect on Satisfaction, which is a big marker of whether someone will continue using the services.  Perceived security doesn't directly affect satisfaction, but it does have a big effect on trust, which then affects continuance intention. These results show how important it is to develop trust and satisfaction in order to keep users loyal in Indonesia's growing superapps mobile banking ecosystem.